Novel green solvent towards scalable fabrication of perovskite solar cell - Muhammad Nauwfhal Mazlan (Nanyang Technological University, 2022)
With huge potential and immense research interest, Perovskite Solar Cell (PSC) is at the forefront of the photovoltaic technology. Its high absorption coefficient, direct band gap structure, flexible and tuneable electronic structure and low fabrication cost has made it a popular research topic. With its photovoltaic performance almost comparable to the commercialise Silicon Photovoltaic technologies, PSC have shown that it is an up-and-coming potential material. Having said that, despite its stellar properties, the toxicity aspects shadow this sustainable technology. As solar energy is supposedly “greener” and more sustainable than conventional fossil fuel, however, the materials used in fabrication are toxic and in particular the commonly used solvent DMF. As such in this report, screening of solvent to identify a novel green solvent without the use of anti-solvent in fabrication was formulated. Additionally, no anti-solvent is a criterion to achieve scalability potential. Studies based on their EHS consideration, ability to dissolve precursors, photophysical properties and photovoltaic performance were evaluated. The results obtained from the screening of potential green solvent is 1-Methoxy-2-Propanol with GBL (co-solvent). This novel green solvent combination was then optimised to find the optimum composition, concentration, MACl concentration and surface passivation compatibility in which 80% 1-Methoxy-2-Propanol at 0.5M and 0.8% MACl additive with no passivation material yields the highest PCE of 11.4%. The result was then compared to a control, where DMF and DMSO solvent combination was fabricated without anti-solvent. The highest PCE recorded for the control is 8.03% indicating that 1-Methoxy-2-Propanol exhibits better photovoltaic performance than the control DMF while remaining “green” and non-toxic.